Strategi Pengembangan Budidaya Udang Vannamei (Litopenaeus Vannamei) Semi Bioflok (Studi Kasus di Balai Layanan Usaha Produksi Perikanan Budidaya Karawang, Jawa Barat) - Satrio, Muhammad Sabdo; Abubakar, Abubakar; Wulandari, Yeni Sari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The semi-biofloc vannamei shrimp (Litopenaeus vannamei) technology is still manual, often having problems such as aeration stones which often fall into ponds and pests in vannamei shrimp disease. This research aims to identify internal (strengths and weaknesses) and external (opportunities and threats) factors that influence vannamei shrimp cultivation strategies. The method used is a case study, analysis using IFAS, EFAS, SWOT, and the Grand Strategy Matrix. There were 10 respondents, including shrimp farmers, traders, people in charge, Fisheries PPLs, experts/experts, Fisheries Services, apprentices, and vannamei shrimp entrepreneurs. Primary data was collected directly through observation and questionnaires, while secondary data was obtained from journal literature and previous research. Purposive sampling is a sampling technique carried out by taking samples from a population based on certain criteria. The research results maximize strengths and opportunities, but simultaneously minimize weaknesses and threats. Recommendations given include maintaining product quality and improving technology such as UV light to prevent dead cells in viruses/bacteria from infecting or spreading widely. Semi-biofloc vannamei shrimp have great potential to produce quality production so that they get higher opinions. The conclusion of this research shows that Vannamei Semi Biofloc Shrimp can improve production quality and increase income.